Analysis of Visitors’ Opinions on Romanian Museums’ Activities - Marius, Surugiu; Raluca, Mazilescu; Camelia, Surugiu (Journal of Tourism Management Research, 2022)
Romanian museums have a rich cultural heritage that is intrinsically valuable to its citizens, however, the number of visitors has been decreasing in recent years as individuals prefer to visit more dynamic and more effectively promoted tourism and cultural establishments. An interactive presence on social media can switch the attention of different cohorts as well as provide a space where people feel free to express their feelings and opinions and thus could also influence the decisions of others in regards to visiting these cultural heritage establishments. This article investigates 1,790 comments posted on Facebook from January to June 2021 by visitors of the Romanian museums to find the emotional responses regarding their experiences. R software delivered the text mining results, sentiment scores, and emotion classifications. In addition, the EViews software was used to produce images regarding the relationships between emotions and sentiments. As a result, we have found that the visitors expressed favorable emotional responses to the Romanian museums’ activities.